Dampak Fatherless Terhadap Perkembangan Emosional Anak Usia Dini - Awallia Romadhona; Cahniyo Wijaya Kuswanto (UIN Sultan Maulana Hasanudin Banten, 2024)
This research aims to investigate the impact of being fatherless or without the direct presence of a father on the emotional development of early childhood. The research procedure involved surveys and data collection through interviews with parents or guardians who care for fatherless early childhood children. In addition, a literature study was carried out to collect information related to the emotional development of early childhood in the context of a fatherless family. The research results show that fatherlessness can have a significant impact on the emotional development of early childhood, including in terms of the formation of interpersonal relationships, psychological well-being, and responses to stress. The implications of these findings for clinical practice and child education are discussed in the context of the need for appropriate support and intervention for children in fatherless situations to ensure healthy and optimal emotional development.